PENGARUH STRUKTUR KEPEMILIKAN DAN KINERJA INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Keuangan di BEI Periode Tahun 2009 â€“ 2011) - Prasetyanto, Pramundityo; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to analyze the relationship between the managerial ownership, institutional ownership, foreign ownership, intellectual capital performance using Pulic models (Value Added Intellectual Coefficient-VAIC â„¢) as a method of quantifying and firm value (Tobin's Q). Is there a relationship between the ownership structure of both managerial ownership, institutional, and foreign and the intellectual capital performance to the firm market value. Data from this study were obtained from financial statements and annual reports of financial companies drawn from the Indonesia Stock Exchange. The population of this study is financial companies listed on the Indonesia Stock Exchange during the years 2009-2011 for 52 companies. Determination of the sample using purposive sampling method. The type of data used are secondary data in the form of annual reports by the media financial companies. The method of analysis used in this study is multiple regression with SPSS computer program. The results of this study show that managerial ownership and institutional ownership of the financial sector companies in Indonesia have no significant effect on firm value (Tobin's Q). However, the ownership that comes from foreign ownership has a significant impact on firm value (Tobin's Q) with the positive direction. The results of this study also indicate that the performance of intellectual capital (VAICTM) have positive effect on firm value (Tobin's Q).